Spatial Distribution of Medium and Large Industries in Driyorejo Subdistrict, Gresik Regency - Faidah, Ana; Wijayanti, Wawargita Permata; Prayitno, Gunawan; Sari, Indah Cahayaning (Journal of Regional and Rural Studies, 2024)
Driyorejo Sub-district in Gresik Regency hosts hundreds of medium and large-scale industries, making it a rapidly expanding industrial corridor that influences local economic development. However, industrial locations vary across all villages, with major investment and labor pockets primarily concentrated near primary collector roads. Such rapid growth has sparked concerns about spatial planning and environmental impacts, prompting an analysis of the industrial distribution patterns. This research aims to identify how these medium and large industries are spatially distributed, given their significant economic, environmental, and spatial influences. A cluster/K-nearest neighbor approach was used to characterize their distribution as random, clustered, or uniform, based on type, number, and specific locations. Results show 3 villages with clustered patterns, 9 villages with random (uneven) distribution, and 4 villages with uniform (even) distribution. These patterns affect physical infrastructure and community socio-economic activities, with uniform patterns indicating broader dispersal and higher local impact. Research limitations include focusing solely on medium and large industries and analyzing only the spatial distribution rather than broader supply-chain or policy dimensions. These findings highlight the need for more balanced industrial planning to manage the interplay between industrial expansion and community well-being.